Wave-absorbing coating material based on nano-porous carbon aerogel and preparation method of wave-absorbing coating material

By preparing nanoporous carbon aerogel and epoxy resin composite materials, the problem of insufficient radar wave absorption performance of existing wave absorbing materials is solved, and excellent wave absorption performance and good durability within high frequency bandwidth are achieved.

CN119570335APending Publication Date: 2025-03-07ARMY ENG UNIV OF PLA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411809325.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing absorbing materials have insufficient performance in radar wave absorption, especially in terms of frequency bandwidth and absorption strength, which are difficult to meet high-demand stealth applications.

Method used

Nanoporous carbon aerogel is used as the basic material, resorcinol and formaldehyde are used as the precursor raw materials, combined with F68 polyether polyol and nickel acetate, and sol-gel method and improved carbonization process are used to prepare nanoporous carbon aerogel composite magnetic metal nickel, and heat-mixed with epoxy resin to form an absorbent coating material.

Benefits of technology

This material exhibits excellent wave absorption performance in common frequency bands of radar, has good temperature, humidity, corrosion resistance and other properties, and is suitable for stealth applications with high frequency bandwidth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570335A_ABST
    Figure CN119570335A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a wave-absorbing coating material based on nano-porous carbon aerogel, which comprises the following steps: A, preparing the nano-porous carbon aerogel by taking resorcinol and formaldehyde as precursor raw materials, absolute ethyl alcohol as a solvent and F68 polyether polyol as a surfactant through acid-base catalysis and adding nickel acetate as a magnetic metal source; and B, thermally mixing and curing the nano-porous carbon aerogel prepared in the step A and epoxy resin to prepare the wave-absorbing coating material based on the nano-porous carbon aerogel. The defects in the prior art can be overcome, the specific surface area of the material is large, the pore structure is adjustable, and the good wave absorbing performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wave-absorbing composite materials, in particular to a wave-absorbing coating material based on nanoporous carbon aerogel and a preparation method thereof. Background Art

[0002] In recent years, battlefield perception technology has become increasingly mature. The battlefield perception system composed of long- and short-term radar networks, air early warning systems, underwater sonar systems, space reconnaissance satellites, and near-field infrared detection systems has woven a three-dimensional, multi-dimensional, and full-area reconnaissance intelligence network on the battlefield. It poses a serious threat to various highly informationized and high-precision offensive means, and also brings unprecedented challenges to the battlefield survival of various weapon platforms and individual soldiers. High-quality and efficient stealth capability has become an important technical condition for whether weapons and equipment and personnel can exert stable combat effectiveness in wartime.

[0003] At present, radar and infrared detection are still the main means of battlefield perception, and stealth technology for radar and infrared detection has also become an important topic for coping with highly transparent battlefields. The research direction mainly focuses on appearance design, stealth materials and electronic countermeasures. However, due to the limitations of the target's appearance and other performance, appearance design and electronic countermeasures have their limitations, and the technology is complex and expensive. Stealth materials have the advantages of strong operability and low cost, which makes them widely studied and applied. Among them, absorbing materials have in-depth mechanism research and relatively mature application technology.

[0004] Absorbing materials achieve "stealth" by mixing and designing the matrix, absorbing and transparent materials to reduce the target's scattering cross section (RCS) of radar waves. The general requirements for absorbing materials are thin coating, light weight, wide bandwidth, strong absorption, and good temperature resistance, moisture resistance, corrosion resistance and other properties. It is not difficult to see from the unique structure and basic properties of carbon aerogel materials that it can meet most of the requirements of stealth materials, and it is expected to develop new absorbing materials based on carbon aerogel. At present, the research on carbon-based aerogel absorbing materials is at a critical stage, and a large number of research results have been applied to various fields. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a microwave absorbing coating material based on nanoporous carbon aerogel and a preparation method thereof. The material has a large specific surface area, an adjustable pore structure and good microwave absorbing performance.

[0006] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows.

[0007] A method for preparing a microwave absorbing coating material based on nanoporous carbon aerogel comprises the following steps:

[0008] A. Resorcinol and formaldehyde are used as precursor raw materials, anhydrous ethanol is used as solvent, F68 Polyether polyol is used as a surfactant, and nanoporous carbon aerogel is prepared by acid-base catalysis and the addition of nickel acetate as a magnetic metal source.

[0009] B. The nanoporous carbon aerogel prepared in step A is thermally mixed and cured with epoxy resin to prepare a microwave absorbing coating material based on the nanoporous carbon aerogel.

[0010] Preferably, in step A, preparing the nanoporous carbon aerogel comprises the following steps:

[0011] A1. Use resorcinol and formaldehyde as precursor raw materials, mix them in a molar ratio of 1:2, use anhydrous ethanol as solvent, stir until they are completely dissolved, and then add F in a molar ratio of 1:100. 68 Polyether polyol is used as a binder, and then acetic acid is added as a catalyst at a molar ratio of 1:600, and finally nickel acetate is added as a metal source, and the molar ratio of nickel acetate to resorcinol is 1:10. The mixture is stirred in a constant temperature water bath at 45°C until a green transparent solution is obtained, and then placed in a test tube and sealed;

[0012] A2. The sealed mixed solution was ultrasonically oscillated for 10 minutes at room temperature, and then kept in a 60°C shaking water bath at a constant temperature of 100 r / min. The reaction solution gradually solidified to form a flesh-colored transparent hydrogel. After complete solidification, the shaking was turned off and the solution was kept at a constant temperature for 3 days to form a wet gel with a stable structure.

[0013] A3. Use anhydrous ethanol as the solvent exchange agent to exchange the water in the wet gel with ethanol. Replace with clean ethanol before each exchange, ultrasonically vibrate for 10 minutes, and place it in a fume hood. The total number of exchanges is 3 days, twice a day;

[0014] A4, using the normal pressure drying method, directly placing the flesh-colored wet gel in a constant temperature blast drying oven, the temperature is controlled at 60°C, the drying time is 3 days, and a dry gel is prepared;

[0015] A5, placing the dry gel in a tubular furnace for carbonization to obtain a carbon aerogel;

[0016] A6. The carbon aerogel was oxidized at 400°C for 1 hour.

[0017] Preferably, in step A5, the dry gel is placed in a quartz tube, pushed into the middle of the tube furnace, evacuated and heated to 150°C within 30 minutes, and kept at a constant temperature for 2 hours under the evacuated state; then an inert gas is filled to increase the pressure in the quartz tube to 3.5 bar, and then heated to 700°C at a rate of 10°C / min and kept at a constant temperature for 4 hours, then evacuated again, and then heated to 800°C at a rate of 20°C / min and kept at a constant temperature for 1 hour, and finally an inert gas is filled to break the vacuum to normal pressure, and heating is stopped for natural cooling to obtain carbon aerogel.

[0018] Preferably, in step B, the preparation process of the microwave absorbing coating material based on nanoporous carbon aerogel comprises the following steps:

[0019] Weigh epoxy resin and preheat it in a water bath at 70°C for 15 minutes to increase its fluidity, then add carbon aerogel powder. Use an electric stirrer to stir for 30 minutes to mix evenly, the mass ratio of epoxy resin to carbon aerogel powder is 10:1; then wait for the resin to cool to room temperature, add polyamide 650 as a curing agent at a mass ratio of 10:9, stir for 15 minutes to obtain a uniform coating, shake the cured resin at a shaking rate of 100r / min for 15 minutes, exhaust the gas and seal it at room temperature for use.

[0020] A microwave absorbing coating material based on nanoporous carbon aerogel is prepared by the preparation method according to any one of claims 1 to 4.

[0021] The beneficial effects brought about by adopting the above technical solution are:

[0022] 1. Aiming at the inherent defect of poor magnetic conductivity of pure carbon aerogel, the sol-gel method was adopted and the carbonization process was improved to prepare nanoporous carbon aerogel with composite magnetic metal nickel. Through structural characterization and absorption performance testing, it was verified that the material exhibited excellent absorption performance in the commonly used radar frequency bands.

[0023] 2. Based on the excellent wave-absorbing properties of carbon aerogel and the high-strength bonding properties of epoxy resin, carbon aerogel / epoxy resin composite coating materials were prepared by hot mixing method, providing technical support for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the thermogravimetric analysis curve of the dried gel.

[0025] Figure 2 This is an electron microscope photo of carbon aerogel that has been carbonized at 150°C for 2 hours.

[0026] Figure 3 This is an electron microscope photo of carbon aerogel that has been carbonized at 700°C for 4 hours.

[0027] Figure 4 This is an electron microscope photo of carbon aerogel after complete carbonization.

[0028] Figure 5 It is the XRD spectrum of the sample prepared by the present invention and three comparative samples.

[0029] Figure 6 It is the nitrogen adsorption isotherm diagram of the sample prepared by the present invention and three comparative samples.

[0030] Figure 7 is the DFT pore size distribution diagram of CA sample.

[0031] Figure 8 It is the DFT pore size distribution diagram of CA / Ni sample.

[0032] Fig. 9 It is the DFT pore size distribution diagram of CA / NiO-1 sample.

[0033] Fig.10 It is the DFT pore size distribution diagram of the CA / NiO-2 sample prepared in the present invention.

[0034] Fig.11 It is a curve diagram of the real part (ε') and imaginary part (ε") of the dielectric constant of the sample prepared by the present invention changing with frequency.

[0035] Fig.12 It is a graph showing the real part (μ') and imaginary part (μ") of the magnetic permeability of the sample prepared by the present invention as a function of frequency.

[0036] Fig.13 The sample C prepared by the present invention o A graph of the value as it changes with frequency.

[0037] Fig.14 is the dielectric loss tangent value (tanδ ε =ε″ / ε′) and magnetic loss tangent (tanδ μ =μ″ / μ′) versus frequency.

[0038] Fig.15 This is a curve showing how the reflection loss of sample number a0 changes with frequency.

[0039] Fig.16 This is a curve showing how the reflection loss of sample number a1 changes with frequency.

[0040] Fig.17 This is a curve showing how the reflection loss of sample number a2 changes with frequency.

[0041] Fig.18 This is a curve showing how the reflection loss of sample number a3 changes with frequency.

[0042] Fig.19 This is a curve showing how the reflection loss of sample A4 changes with frequency.

[0043] Fig. 20 This is the thermal infrared image of the A0 labeled sample.

[0044] Fig.21 This is the thermal infrared image of the A1-labeled sample.

[0045] Fig. 22 This is the thermal infrared image of the A2-labeled sample.

[0046] Fig.23 This is the thermal infrared image of the A3 labeled sample.

[0047] Fig.24 This is the thermal infrared image of the A4-labeled sample. DETAILED DESCRIPTION

[0048] First, prepare the nanoporous carbon aerogel:

[0049] Resorcinol and formaldehyde were used as precursor materials, mixed at a molar ratio of 1:2, anhydrous ethanol was used as solvent, stirred until they were completely dissolved, and F was added at a molar ratio of 1:100. 68 Polyether polyol is used as a binder, and then acetic acid is added as a catalyst in a molar ratio of 1:600, and finally nickel acetate is added as a metal source, and the molar ratio of nickel acetate to resorcinol is 1:10. After stirring evenly in a constant temperature water bath at 45°C to a green transparent solution, it is placed in a test tube and sealed.

[0050] At room temperature, the sealed mixed solution was ultrasonically oscillated for 10 minutes. Ultrasound can increase the gel curing rate, and the possible oxidation process of phenolic compounds can also be effectively inhibited to form a uniform and transparent organic aerogel, which can improve the quality of the aerogel. Then, the reaction was kept at a constant temperature in a 60°C shaking water bath with an oscillation rate of 100r / min; the reaction solution gradually solidified to form a flesh-colored transparent hydrogel. After it was completely solidified, the shaking was turned off and the solution was kept at a constant temperature for 3 days to form a wet gel with a stable structure.

[0051] Anhydrous ethanol was used as the solvent exchange agent to exchange the water in the wet gel with ethanol. Clean ethanol was replaced before each exchange, ultrasonically shaken for 10 minutes, and placed in a fume hood. The total number of exchanges was 3 days, with exchanges twice a day.

[0052] The flesh-colored wet gel was directly placed in a constant temperature blast drying oven with the temperature controlled at 60°C and the drying time was 3 days to prepare the dry gel. 68Polyether polyols can effectively prevent shrinkage caused by excessive external pressure during normal pressure processes.

[0053] The dry gel is placed in a tubular furnace for carbonization. Specifically, the dry gel is placed in a quartz tube, pushed into the middle of the tubular furnace, evacuated and heated to 150°C within 30 minutes, and kept at a constant temperature for 2 hours under evacuated conditions; then inert gas is filled to increase the pressure in the quartz tube to 3.5 bar, and then heated to 700°C at a rate of 10°C / min and kept at a constant temperature for 4 hours, then evacuated again, and then heated to 800°C at a rate of 20°C / min and kept at a constant temperature for 1 hour, and finally inert gas is filled to break the vacuum to normal pressure, and heating is stopped for natural cooling to obtain carbon aerogel.

[0054] The carbon aerogel was oxidized at 400°C for 1 hour. Nickel mainly exists in the form of metal Ni. Since NiO can produce a large specific capacity in the electrochemical reaction, the sample was subjected to low-temperature oxidation heat treatment to completely convert Ni into NiO, producing a large specific capacitance.

[0055] Nanoporous carbon aerogel performance testing.

[0056] Figure 1 This is the thermogravimetric analysis curve of the dried dry gel sample. It can be found from the figure that the sample has two weight loss situations: 25-400℃, a small amount of weight loss in this stage is caused by the evaporation of the remaining water in the sample; 400-630℃, this stage has a significant weight loss, there are two cases of mass change; one is mainly the high temperature decomposition of C; the other is the increase in the mass of metal Ni turning into NiO. From 25-1000℃, the total mass loss is 70.41%. When the temperature reaches 630℃, C has been completely decomposed, and until the following 1000℃, the mass has not changed, and a stable structure has been achieved. Another hidden mass change is the transformation of metal Ni to NiO, with a small mass increase. This can be seen from the DSC diagram. There is an obvious phase transition process. This temperature is just right for metal Ni to be converted into NiO, but the overall process still shows a downward trend, only because the mass loss of C is significantly greater than the increase in Ni.

[0057] Figure 2-Figure 4These are electron microscope photos of the three stages of the carbonization process of carbon aerogel. It can be seen that as the carbonization process proceeds, the voids in the material gradually become larger, and the connection structure between the voids gradually becomes coarser. This is because the first stage of the carbonization process is mainly to remove the residual water in the material, the second stage is to modify the carbon chain structure in the material through high temperature and high pressure, and the third stage is mainly to merge and thicken the carbon chain structure. After the above carbonization treatment, the distribution state of metal Ni in the carbon aerogel can be optimized, the magnetic loss factor of the material can be increased, and the mesoporous area of ​​the material can be increased, thereby improving the absorption capacity of radar waves.

[0058] Figure 5 In the figure, CA is a carbon aerogel sample without metal Ni doping, CA / Ni is a carbon aerogel sample doped with metal Ni but not oxidized, CA / NiO-1 is a carbon aerogel sample oxidized for 0.5 h, and CA / NiO-2 is a sample that has completed all the processing steps of the present invention. There are two broadened diffraction peaks in the spectrum of CA, located at 24.7° and 43°, corresponding to (002) and (101), respectively, which are characteristic peaks of carbon materials. From CA / Ni, it can be seen that in addition to the characteristic peak (002) of carbon materials, obvious diffraction peaks appear at 44.5°, 51.8°, and 76.4°, corresponding to (111)(220)(220) crystal planes, respectively, without obvious impurity peaks, corresponding to the PDF standard card 65-2865 of metal Ni, indicating the presence of metal Ni. From the XRD patterns of CA / NiO-1 and CA / NiO-2, it can be found that the characteristic peaks of 37.2°, 43.3°, 62.9°, 75.4°, and 79.4° correspond to the crystal planes of (111), (200), (220), (311), and (222), respectively, indicating the presence of NiO (standard PDF card 47-1049). As the oxidation heat treatment process proceeds, NiO gradually appears and metallic Ni slowly disappears. From the above four groups of spectra, it can be found that although the quality of the carbon material has been lost, the loss is small at 400°C, and the carbon peak does not change much from the XRD spectrum.

[0059] The following table shows the analysis of the Ni content in the samples using different analysis methods.

[0060] It can be seen from the table that the measured contents are very close to the theoretical values.

[0061]

[0062] Depend on Figure 6It can be found that the adsorption isotherms are all type IV, and the adsorption loops are close to the H1 loops of type IV, indicating that there are narrow pore structures in carbon aerogels and their composite materials, which are evenly distributed throughout the material. The adsorption curves of the samples at low relative partial pressures are type I, indicating that there are a large number of micropores in the structure of all carbon aerogel samples. The hysteresis loops in the high partial pressure region indicate the presence of mesopores, and Figure 6 The distribution is consistent. It can be seen from the figure that the pore distribution types of CA and CA / Ni samples are very similar, so the specific surface areas are basically the same. While the micropores of CA / NiO-1 and CA / NiO-2 samples are increasing, a large number of mesopores are also increasing, and the specific surface area is significantly increased.

[0063] Figure 7-10 The DFT pore size distribution diagram shows that different samples show multi-peak distribution, which is concentrated in micropores <2nm and mesopores in the range of 2.5-5nm, and the pore distribution strength varies with different samples. The pore volume peak intensities of CA and CA / Ni samples in the micropore range of <2nm and the mesopore range of 2.5-5nm are similar, with only slight differences, indicating that their specific surface areas are not much different. The CA / NiO-1 sample has a sharp pore volume distribution peak in the micropore range <2nm, indicating that there are a large number of micropores. Compared with the CA / NiO-2 sample, the number of micropores is larger, resulting in a smaller average pore size and pore volume. The amount of micropores in CA / NiO-2 decreases and the mesopores increase, so the specific surface area increases. This is all due to the partial collapse of the micropores during the oxidation heat treatment, forming a large number of mesopores. See the table below for data comparison.

[0064]

[0065]

[0066] from Fig.11 It can be seen that the values ​​of ε' and ε" decrease with increasing frequency. For most carbon-based materials, dielectric loss comes from polarization loss and conductive loss, where polarization loss includes dipole polarization, interface polarization, etc., and conductive loss comes from electron migration.

[0067] from Fig.12 It can be seen that its magnetic permeability also decreases with the increase of frequency.

[0068] C0 is calculated using the formula C0 = μ″(μ′) -2 f -1It is described as the contribution of eddy current loss to magnetic permeability. Generally speaking, magnetic loss comes from exchange resonance, ferromagnetic resonance, eddy current, hysteresis, domain wall effect, etc. Among them, hysteresis and domain wall effect are negligible in the range of 2-18GHz. Therefore, the magnetic loss of the material is controlled by exchange resonance, natural ferromagnetic resonance and eddy current loss. If the C0 value remains constant in the range of 2-18GHz, eddy current loss makes the main contribution to magnetic loss. From Fig.13 It can be seen that the C0 value of the material changes from positive to negative, so the magnetic loss of the material not only comes from eddy current loss, but also from exchange resonance and natural ferromagnetic resonance.

[0069] Dielectric loss tangent (tanδ ε =ε″ / ε′) and magnetic loss tangent (tanδ μ =μ″ / μ′) versus frequency. These two values ​​represent the dielectric loss and magnetic loss capabilities, respectively. Fig.14 It can be seen that in the range of 2-18Ghz, the tanδ of the material ε The value is always greater than tanδ μ The value indicates that the dielectric loss of the material plays a dominant role in the electromagnetic wave loss process.

[0070] As the thickness increases, the maximum absorption peaks of all materials gradually move to the low-frequency region. This change pattern satisfies the 1 / 4 wavelength law. Therefore, the reflection loss value and the absorption wave frequency range can be effectively adjusted by adjusting the thickness of the nanoporous carbon aerogel to achieve electromagnetic wave absorption in different frequency bands. When the frequency is 16.0GHz and the coating thickness is only 1.6mm, the RLmin value is -47.9dB. In the low-frequency region (7.3GHz), at a thickness of 3.0mm, it can also show good electromagnetic wave absorption performance (-40.9dB). This shows that the nanoporous carbon aerogel prepared by the present invention has good wave absorption performance.

[0071] Comparative analysis of the microwave absorbing effects of microwave absorbing coating materials based on nanoporous carbon aerogel.

[0072] In order to test the absorbing performance of the prepared coating and explore the effect of aerogel content on the absorbing performance, 5 types of coating films a0 to a4 were prepared. 8g of coating was weighed each time to cover the entire plastic dish, and the coating surface was kept flat. After curing and drying at room temperature, a uniform coating film was obtained. Among them, a0 was pure epoxy resin as a blank control. The contents of nanoporous carbon aerogels in the 5 coatings are shown in the table below.

[0073] serial number a0 a1 a2 a3 a4 Aerogel mass fraction / % 0 3 6 9 10

[0074] Depend on Figure 15-19It can be seen that the a0 control sample has no effective absorption bandwidth, but after adding 3% CA / NiO, the absorption performance of the composite coating material is improved; when 6% CA / NiO is added, the reflection loss value of the composite coating material at 8.2GHz is -18.6dB, and the effective absorption bandwidth is 2.12GHz; when 9% CA / NiO is added, the composite coating material shows good absorption performance, and when the coating is 3.3mm, the reflection loss value at 8.0GHz reaches -43.8dB, and the effective absorption bandwidth is 3.27GHz; when 10% CA / NiO is added, its absorption performance is the best, and when the coating is 2.1mm, the reflection loss value at 13.92GHz reaches -44.1dB, and the effective absorption bandwidth at high frequency reaches 4.13GHz. Through the comparative analysis of the five materials and CA / NiO, it is not difficult to see that EP has a certain influence on the absorption performance of CA / NiO, but with the change of the amount of CA / NiO added, it shows different effects.

[0075] Preparation and comprehensive performance study of CA / NiO / EP coating camouflage materials.

[0076] The above five different CA / NiO / EP coatings were evenly coated on the surface of a 20 cm×20 cm polyester fabric. Each material was coated five times, with 24 g applied each time, to obtain CA / NiO / EP coating camouflage materials A0 to A4.

[0077] The tensile properties of the camouflage material were tested at a tensile speed of 2 mm / min, where the sample was 200 mm long, 200 mm wide, and 2.1 mm (± 0.1) thick; the bending properties of the camouflage material were tested at a loading speed of 20 mm / min, where the sample was 200 mm long, 200 mm wide, and 2 mm (± 0.1) thick, with a span of 40 mm.

[0078] The tensile strength and flexural strength of the camouflage material A0 without adding aerogel are 33.10MPa and 102.54MPa. When 3% aerogel is added, the tensile and flexural strengths of the camouflage material A1 increase to 35.42MPa and 112.43MPa, respectively, an increase of 7% and 9.6%; when 6% aerogel is added, the tensile strength and flexural strength of the camouflage material A2 decrease to 29.98MPa and 98.65MPa, respectively, a decrease of 9.4% and 3.8%, respectively; when 9% aerogel is added, the tensile strength and flexural strength of the camouflage material A3 decrease to 20.52MPa and 88.75MPa, respectively, a decrease of 38% and 13.4%, respectively; when 10% aerogel is added, the tensile strength and flexural strength of the camouflage material A4 decrease to 18.48MPa and 76.09MPa, a decrease of 44.2% and 25.8%, respectively.

[0079] Turn on the constant temperature heating table and raise the temperature to 50°C. Spread the sample material flat on the constant temperature heating table. After 5 minutes, use a thermal infrared imager to shoot vertically. Keep the distance between the thermal imager and the sample at 1m each time. Import the captured thermal infrared image into the FLIR Tools software. The software can be used to obtain the thermal infrared radiation temperature of different areas of the image. By comparing the image color difference and infrared radiation temperature difference between the sample material surface and the surrounding environment in different images, the infrared stealth performance can be compared. The smaller the image color difference and infrared radiation temperature difference, the better the infrared stealth effect of the material. Figure 20-24 It can be seen that the image color difference and infrared radiation temperature difference between the surface of composite materials A0~A4 and the surrounding environment gradually decrease, and the infrared radiation temperature differences are 8.5℃, 6.9℃, 4.2℃, 3.0℃, and 2.0℃, respectively. That is, with the increase of aerogel content, the infrared stealth effect of the composite material gradually improves, and shows the same size law as the corresponding thermal conductivity of the coating film. Therefore, reducing the thermal conductivity of the material can effectively improve the infrared stealth performance of the material under certain conditions.

[0080] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a microwave absorbing coating material based on nanoporous carbon aerogel, characterized in that: The following steps are included: A. Resorcinol and formaldehyde are used as precursor raw materials, anhydrous ethanol is used as solvent, F 68 Polyether polyol is used as a surfactant, and nanoporous carbon aerogel is prepared by acid-base catalysis and the addition of nickel acetate as a magnetic metal source. B. The nanoporous carbon aerogel prepared in step A is thermally mixed and cured with epoxy resin to prepare a microwave absorbing coating material based on the nanoporous carbon aerogel.

2. The method for preparing the microwave absorbing coating material based on nanoporous carbon aerogel according to claim 1, characterized in that: In step A, preparing nanoporous carbon aerogel comprises the following steps: A1. Use resorcinol and formaldehyde as precursor raw materials, mix them in a molar ratio of 1:2, use anhydrous ethanol as solvent, stir until they are completely dissolved, and then add F in a molar ratio of 1:

100. 68 Polyether polyol is used as a binder, and then acetic acid is added as a catalyst at a molar ratio of 1:600, and finally nickel acetate is added as a metal source, and the molar ratio of nickel acetate to resorcinol is 1:

10. The mixture is stirred in a constant temperature water bath at 45°C until a green transparent solution is obtained, and then placed in a test tube and sealed; A2. The sealed mixed solution was ultrasonically oscillated for 10 minutes at room temperature, and then kept in a 60°C shaking water bath at a constant temperature of 100 r / min. The reaction solution gradually solidified to form a flesh-colored transparent hydrogel. After complete solidification, the shaking was turned off and the solution was kept at a constant temperature for 3 days to form a wet gel with a stable structure. A3. Use anhydrous ethanol as the solvent exchange agent to exchange the water in the wet gel with ethanol. Replace with clean ethanol before each exchange, ultrasonically vibrate for 10 minutes, and place it in a fume hood. The total number of exchanges is 3 days, twice a day; A4, using the normal pressure drying method, directly placing the flesh-colored wet gel in a constant temperature blast drying oven, the temperature is controlled at 60°C, the drying time is 3 days, and a dry gel is prepared; A5, placing the dry gel in a tubular furnace for carbonization to obtain a carbon aerogel; A6. The carbon aerogel was oxidized at 400°C for 1 hour.

3. The method for preparing the microwave absorbing coating material based on nanoporous carbon aerogel according to claim 2, characterized in that: In step A5, the dry gel is placed in a quartz tube, pushed into the middle of the tubular furnace, evacuated and heated to 150°C within 30 minutes, and kept at a constant temperature for 2 hours under the evacuated state; then an inert gas is filled to increase the pressure in the quartz tube to 3.5 bar, and then heated to 700°C at a rate of 10°C / min and kept at a constant temperature for 4 hours, then evacuated again, and then heated to 800°C at a rate of 20°C / min and kept at a constant temperature for 1 hour, and finally an inert gas is filled to break the vacuum to normal pressure, and heating is stopped for natural cooling to obtain carbon aerogel.

4. The method for preparing the microwave absorbing coating material based on nanoporous carbon aerogel according to claim 3, characterized in that: In step B, the preparation process of the microwave absorbing coating material based on nanoporous carbon aerogel includes the following steps: Weigh epoxy resin and preheat it in a water bath at 70°C for 15 minutes to increase its fluidity, then add carbon aerogel powder. Use an electric stirrer to stir for 30 minutes to mix evenly, the mass ratio of epoxy resin to carbon aerogel powder is 10:1; then wait for the resin to cool to room temperature, add polyamide 650 as a curing agent at a mass ratio of 10:9, stir for 15 minutes to obtain a uniform coating, shake the cured resin at a shaking rate of 100r / min for 15 minutes, exhaust the gas and seal it at room temperature for use.

5. A microwave absorbing coating material based on nanoporous carbon aerogel, characterized in that: The preparation method is described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Carbon aerogel for electric adsorption electrode and preparation method for carbon aerogel

    CN103721645A

  • Double-layer wave absorbing coating material and preparation method thereof

    CN108587395A

  • Preparing method of coated type stealth coating

    CN110711688A

  • Composite material and preparation method thereof

    CN111423205A